On Extrapolation Cascadic Multigrid Method (Journal of Computational Mathematics, 2021)
Based on an asymptotic expansion of (bi)linear finite elements, a new extrapolation formula and extrapolation cascadic multigrid method (EXCMG) are proposed. The key ingredients of the proposed methods are some new extrapolations and quadratic interpolations, which are used to provide better initial values on the refined grid. In the case of triple grids, the errors of the new initial values are analyzed in detail. The numerical experiments show that EXCMG has higher accuracy and efficiency.